Humor Improves Women’s but Impairs Men’s Iowa Gambling Task Performance - Flores-Torres, Jorge; Gómez-Pérez, Lydia; McRae, Kateri; López, Vladimir; Rubio, Ivan; Rodríguez, Eugenio (Frontiers in Psychology, 2019)
The Iowa Gambling Task (IGT) is a popular method for examining real-life decision-making. Research has shown gender related differences in performance, in that men consistently outperform women. It has been suggested that these performance differences are related to decreased emotional control in women compared to men. Given the likely role of emotion in these gender differences, in the present study we examine the effect of a humor induction on IGT performance and whether the effect of humor is moderated by gender. IGT performance and parameters from the Expectancy Valence Model were measured in 68 university students (34 men; mean age 22.02, SD = 4.3 and 34 women; mean age 22.3, SD = 4.1) during a 100 trial-IGT task. Participants were exposed to a brief video before each of the IGT decisions available; one half of the sample (17 men and 17 women) was exposed to 100 humor videos, while the other half was exposed to 100 non-humor videos during the task. We observed a significant interaction between gender and humor, such that under humor, women’s performance during the last block (trials 80-100) improved (compared to women under non-humor), whereas men’s performance during the last block was worse (compared to men under non-humor). Consistent with previous work, under non-humor, men outperformed women in the last block. Lastly, our EVM results show that humor impacts the learning mechanisms of decision-making differently in men and women. Humor impaired men’s ability to acquire knowledge about the payoff structure of the decks, and as a consequence they were stuck in suboptimal performance. On the other hand, humor facilitated women’s ability to explore and to learn from experience, improving performance. These findings deepen our understanding of the mechanisms underlying IGT decision-making and differential effects of humor in men and women.